Novel fibrin functionalized multilayered electrospun nanofiber membrane for burn wound treatment - Talukder, Md Eman; Hasan, K. M. Faridul; Wang, Jianming; Yao, Jingbo; Li, Caolong; Song, Hongchen (Journal of materials science, 2021)
In this study, a novel hybrid multilayered electrospun nanocomposite membrane (MENM) was developed for activated wound dressing applications. An established electrospinning process was employed to fabricate a tri-layer nanocomposite membrane where the lower layer was composed of chitosan (CS)/polyvinyl alcohol (PVA) and fibrin (having regeneration of tissues and bleeding resistance properties), both of which are directly in contact with the burn wound (BW) skin, and a middle layer of PVA/sodium alginate (SA) (having antibacterial properties). The top layer consisted of gelatin (super hydrophilic properties). The MENM morphology was characterized by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) which confirmed the presence of the elemental and chemical structures of MENM. The MENM was identified by Fourier transform infrared spectroscopy (FTIR) with a maximum drug release which was ascended within 10-h duration. X-ray diffraction (XRD) showed long-term absorbency due to the presence of more amorphous and less crystallinity percentages in the MENM. The nanocomposites' thermal stability was also observed via thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The developed MENM has shown excellent antibacterial activity with a zone of inhibition of 18.7 ± 0.9 mm, 18.9 ± 0.9 mm, 20.0 ± 1 mm and 19.3 ± 0.9 mm, respectively, against Escherichia coli ( E. coli ) and Staphylococcus aureus (S. aureus) bacteria. The high water absorbant properties of MENM indicate that the produced membranes could absorb the maximum exudate from wounded skin within the shortest time and assist in healing the wound quickly. The produced MENMs could be potential wound dressing materials in the future. Graphical abstract